An agent-oriented approach to holistic sustainability reporting. (2015) - Hickmott, Sarah; Magee, Liam; Thom, James; Padgham, Lin
This paper presents a software application for sustainability reporting where a multi-agent system is an integral part of the overall architecture. We describe the social science philosophy and approach on which the application is based, and the ways in which an agent-based system is able to support these. In particular, we explore how the pro-active, goal oriented, context sensitive nature of the agent system is able to realise the principles of the underlying philosophy, which are to encourage holistic monitoring of sustainability and balance user relevance with standardisation. Further to the functional benefits, the paper looks at why agent oriented design is also valuable as a communication tool in the multi-disciplinary team, enabling the non-computer science members to be actively engaged in system design.